Greenhouse gas emissions from the energy crop oilseed rape (Brassica napus); the role of photosynthetically active radiation in diurnal N2O flux variation. Issue 5 (19th December 2017) - Keane, Ben J.; Ineson, Phil; Vallack, Harry W.; Blei, Emanuel; Bentley, Mark; Howarth, Steve; McNamara, Niall P.; Rowe, Rebecca L.; Williams, Mat; Toet, Sylvia
Abstract: Oilseed rape (OSR, Brassica napus L.) is an important feedstock for biodiesel; hence, carbon dioxide (CO2 ), methane (CH4 ) and particularly fertilizer‐derived nitrous oxide (N2 O) emissions during cultivation must be quantified to assess putative greenhouse gas (GHG) savings, thus creating an urgent and increasing need for such data. Substrates of nitrification [ammonium (NH4 )] and denitrification [nitrate (NO3 )], the predominant N2 O production pathways, were supplied separately and in combination to OSR in a UK field trial aiming to: (i) produce an accurate GHG budget of fertilizer application; (ii) characterize short‐ to medium‐term variation in GHG fluxes; (iii) establish the processes driving N2 O emission. Three treatments were applied twice, 1 week apart: ammonium nitrate fertilizer (NH4 NO3, 69 kg‐N ha −1 ) mimicking the farm management, ammonium chloride (NH4 Cl, 34.4 kg‐N ha −1 ) and sodium nitrate (NaNO3, 34.6 kg‐N ha −1 ). We deployed SkyLine2D for the very first time, a novel automated chamber system to measure CO2, CH4 and N2 O fluxes at unprecedented high temporal and spatial resolution from OSR. During 3 weeks following the fertilizer application, CH4 fluxes were negligible, but all treatments were a net sink for CO2 (ca. 100 g CO2  m −2 ). Cumulative N2 O emissions (ca. 120 g CO2 ‐eq m −2 ) from NH4 NO3 were significantly greater ( P  < 0.04) than from NaNO3 (ca. 80 g CO2 ‐eq m −2 ), but did not differ from NH4 Cl (ca. 100 g CO2 ‐eq m −2 ) and reduced the carbon sink of photosynthesis so that OSR was a net GHG source in the fertilizer treatment. Diurnal variation in N2 O emissions, peaking in the afternoon, was more strongly associated with photosynthetically active radiation (PAR) than temperature. This suggests that the supply of carbon (C) from photosynthate may have been the key driver of the observed diurnal pattern in N2 O emission and thus should be considered in future process‐based models of GHG emissions. Abstract : In our field study, we quantified greenhouse gas (GHG) emissions from OSR ( Brassica napus ), using new technology SkyLine2D. Three treatments, applied twice, 1 week apart, were as follows: ammonium nitrate fertiliser (NH4 NO3, 69 kg‐N ha −1 ) mimicking the farm management, ammonium chloride (NH4 Cl, 34.6 kg‐N ha −1 ) and sodium nitrate (NaNO3, 34.4 kg‐N ha −1 ). CH4 fluxes were negligible, and all treatments were a net sink for CO2 (ca. 100 g CO2  m −2 ). N2 O emissions (ca. 120 g CO2 ‐eq m −2 ) reduced the carbon sink of photosynthesis so that OSR was a net GHG source in the NH4 NO3 fertiliser treatment and were significantly greater ( P  < 0.04) than in the NaNO3 treatment which received 50% less N, although this did not reduce biomass or N content of the crop. A strong diurnal pattern of N2 O emissions, peaking during the afternoon, was most closely related to photosynthetically active radiation. We suggest that this relationship indicates that the availability of labile carbon (C) in photosynthate drove denitrification.